(untitled) (Anuario Filosófico, 2018)
A true systematic philosophy can only be, to quote Descartes, a "sagesse humaine". However, this is not a system that opens up to itself beyond what is systematic, being thus likewise capable of explaining in itself the most extreme problems of existence.